2009
DOI: 10.1111/j.1365-2486.2008.01798.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to increasing background ozone impairs stomatal functioning in grassland species

Abstract: Two species found in temperate calcareous and mesotrophic grasslands (Dactylis glomerata and Leontodon hispidus) were exposed to eight ozone treatments spanning preindustrial to post-2100 regimes, and late-season effects on stomatal functioning were investigated. The plants were grown as a mixed community in 14 L containers and were exposed to ozone in ventilated solardomes (dome-shaped greenhouses) for 20 weeks from early May to late September 2007. Ozone exposures were based on O 3 concentrations from a near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 40 publications
1
79
0
Order By: Relevance
“…3). Similar findings were reported in previous studies (e.g., Paoletti, 2005;Mills et al, 2009;Paoletti and Grulke, 2010;Hoshika et al, 2012a). Maier-Maercker (1989) suggested that such slower stomatal response might be explained by delignification of the guard cell and subsidiary cells as recorded in ozonated Picea abies.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…3). Similar findings were reported in previous studies (e.g., Paoletti, 2005;Mills et al, 2009;Paoletti and Grulke, 2010;Hoshika et al, 2012a). Maier-Maercker (1989) suggested that such slower stomatal response might be explained by delignification of the guard cell and subsidiary cells as recorded in ozonated Picea abies.…”
Section: Discussionsupporting
confidence: 89%
“…In manna ash, such slower stomatal responses were considered as accelerated senescence in the cell physiological processes (Paoletti et al, 2009). Mills et al (2009) found that O 3 reduced stomatal sensitivity to ABA. Wilkinson and Davies (2010) suggested that the loss of stomatal response to ABA may be related to O 3 -induced ethylene emissions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, several studies have shown that drought does 29 not always reduce O3 -induced damage to plants in sensitive species (e.g. Mills et al, 2009;30 McLaughlin et al, 2007a;Robinson et al, 1998;Wagg et al, 2012;Wilkinson andDavies, 2009, 31 2010), and that the genetic variability in O3 sensitivity may be related to the extent to which O3 32 reduces the sensitivity of stomatal closure to soil drying. Such effects have been attributed to 1 reduced response to drought signals such as abscisic acid in the presence of ozone-induced stress 2 ethylene emission (Mills et al, 2009;Wilkinson andDavies 2009, 2010).…”
Section: Interactions Between Ozone and Drought 24mentioning
confidence: 99%
“…Despite the often reported decline in stomatal conductance at elevated O3, 25 stimulation of stomatal opening (Mills et al, 2009) and the induction of stomatal sluggishness 26 (Paoletti and Grulke, 2010) have also been observed (discussed later). On the other hand, elevated 27 CO2 reduces stomatal conductance (Curtis and Wang, 1998;Drake et al, 1997;Kim et al, 2010;28 Morgan, 2003) and therefore the uptake of O3 and its damaging impacts on plants (Fiscus et al, 29 1997;Harmens et al, 2007;McKee et al, 1997).…”
mentioning
confidence: 99%